Does artificial grass affect the competitive balance in major league soccer? - Trombley, M. J. (Journal of Sports Analytics, 2016)
In this study I present cause for concern that Major League Soccer teams with an artificial grass (AG) home playing surface may possess an advantage over visiting teams used to playing on grass. I develop a theoretical model predicting the outcomes we should observe if teams with AG possess a competitive advantage. Using match-level data from the 2011-2014 Major League Soccer regular seasons, I find that conditional on attendance, distance traveled, and the difference in talent between the two teams, AG is uncorrelated with the final outcome of a match and the number of goals scored by each team. This suggests that AG does not affect the competitive balance in Major League Soccer.